(Table T1) Sedimentation rate, bulk density and mass accumulation rate of ODP Hole 198-1208A - Susanne Gylesjö (PANGAEA, 2005)
Ocean Drilling Program Leg 198 Site 1208 is located on the Central High of Shatsky Rise (36°7.6301 extquotesingleN, 158°12.0952 extquotesingleE) in the North Pacific Ocean at a water depth of 3346 m. A total of 345.9 m of sediment was recovered from Hole 1208A. The sediment was divided into two major stratigraphic units: Holocene-Paleocene alternating nannofossil clay and nannofossil ooze with diatoms and radiolarians (Unit I, Subunits IA, IB, and IC) and Campanian-Albian nannofossil ooze with minor chert (Unit II). This study reports the terrigenous contribution to Site 1208 for the upper 24 m of Subunit IA, corresponding to ~560 ka.
Supplement to: Gylesjö, S (2005): Data report: Late Pleistocene terrigenous input to Shatsky Rise, Site 1208. In: Bralower, TJ; Premoli Silva, I; Malone, MJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 198, 1-7, https://doi.org/10.2973/odp.proc.sr.198.105.2005